Performance Measurement of university libraries A Case study of the university of education, Winneba (UEW) Library - Jones, W. (University of Ghana, 2010)
This study focused on the performance of the university of education library. The study tested the theory of service quality as proposed by zeithamla et al (1985) who explains the gap between an organization and its customer and their perception and expectation in relation to service quality. They make the point that only customers can judge quality all other judgments are irrelevant. To achieve this aim, the survey methodology was used to survey one hundred and fifteen users of the UEW library. The respondent were made up of fifty two undergraduates students, twenty graduates students, nineteen teaching and fifteen non-teaching staff. The study revealed that, while most of the users rated their perception of library service as either moderate or moderately high. These were not meeting in the most cases their desired or maximum service quality levels. The results further indicated that, the users were not satisfied with the physical facilities, the accuracy and dependability and willingness of staff to provide prompt services. Further even though the employees had a moderately high rating for knowledgeability. Users perceived staff courteousness to be below their desire and maximum service quality level. The same applied to the individualized attention that the various user categories received when they access library services. In addition, the results further indicated a bias by the UEW library in their service to the various user groups. The teaching and the non- teaching staff gave better rating than mostly the undergraduate and sometimes the post graduate students. The study concluded that generally the performance of the UEW library was not meeting the users desired and maximum service quality levels and that does not facilitate quality academic service. Therefore, in order to enhance the performance of the UEW library there is a need for the UEW authorities as a whole and the library in particular to create awareness on importance of and benefit to be derived from service quality performance measurement. The institution of formal performance measurement that see the views of users on how well the library is performing Also, UEW library should process and made aware of the results and its implications. This will ensure that not only will staff embrace the results and see it as a challenge to overcome but will also make the necessary adjustments to improve upon their service.
MA. Library Studies
Keywords: Library; University Libraries; UEW; performance; performance measurement